Fine-tuning word meanings through mobile app and online resources: A case study of strategy use by a hyperpolyglot. (October 2019) - Cohen, Andrew D.; Kai-Hui Wang, Isobel
Abstract: The purpose of this study was to investigate a hyperpolyglot's strategies for fine-tuning his understanding of Chinese vocabulary through mobile apps, online programs, and interactions with a tutor. Videotaped verbal reporting revealed that the subject used strategies for (1) managing vocabulary resources – planning, organizing, and monitoring/evaluating their use, and for (2) processing the information in the resources – finding word equivalents in Chinese for English words, fine-tuning the word meanings and then verifying them. He predominantly used strategies either in sequence or in pairs, sometimes separately, and only occasionally in clusters. While he was successful at fine-tuning 57% of the vocabulary items through accessing selected resources, his fine-tuning efforts still were unsuccessful 43% of the time. The effectiveness of fine-tuning depended on the subject's ability to find the information he needed, to orchestrate the various aspects of word knowledge, and to monitor and evaluate his performance. This case study with one highly experienced language learner applied a close-up lens to the process of vocabulary fine-tuning, and provided insights for researchers and teachers regarding strategies for accessing technology aimed at enhancing vocabulary knowledge.